Resilience in the Endurance Runner: The Role of Self-Regulatory Modes and Basic Psychological Needs - Diotaiuti, Pierluigi; Corrado, Stefano; Mancone, Stefania; Falese, Lavinia (Frontiers in Psychology, 2021)
Endurance sports certainly require an important and delicate task of mental and physical reintegration from the impact of the fatigue induced by the exertion of the sport performance. The topic of the resilience of athletes has been the theme of numerous studies, however there are few specific works on the psychological resilience of runners. Our study aimed to investigate Resilience in Endurance Runner related to the role of Self-Regulation Modes and Basic Psychological Needs. Especially,the aim of our work was presenting a model where the gratification of the Needs of Autonomy and Competence and the level of Locomotion were the predictors of the two main components of Richardson’s resilience: Homeostatic and Resilient Reintegration. The present study involved 750 endurance runners, members of the Fidal (Italian Athletics Federation). A SEM analysis was performed combining into one explanatory model the following variables: Autonomy and Competence Satisfaction, Self-Regulatory Locomotion Mode, Homeostatic and Resilient Reintegration. The model showed overall acceptable fit measurements: 2 = 872.152; CFI = .966; TLI = .952; RMSEA = .058. Results indicated that BPNs and SRMs are predictors of the level of resilience in endurance running athletes. In particular, Resilient Reintegration was mainly affected by Locomotion Mode (𝛽 = .379 for p < .005), which in turn received a major influence from Autonomy Satisfaction (𝛽 = .574 for p < .001). Homeostatic Recovery was found to be affected by Competence Satisfaction (𝛽 = .489 for p < .001). The study pointed out the importance of supporting in endurance runners the gratification of the needs of Autonomy and Competence as key factors capable of enhancing perseverance, timely recovery and psychophysical balance.